Determination of Effective Speech Skills of Pediatric Nurses and Affecting Factors - Sibel Küçükoğlu; Semra Köse; Aynur Aytekin Özdemir; Neşe Taşkıran (Galenos Yayinevi, 2018)
Aim: This descriptive and cross-sectional research aims to determine effective speech skills of pediatric nurses and their affecting factors. Materials and Methods: The study population consisted of 124 nurses working in pediatric clinics of one university hospital, two state hospitals and two private hospitals located in the Province of Erzurum, Turkey. The research data were obtained using a "Demographic Information Form" and an "Effective Speech scale (ESS)". In the analysis of the data, percentile distributions, averages, t-test, One-Way variance analysis, Kruskal-Wallis variance analysis and Cronbach's alpha coefficient were used. Ethical principles were adhered to when conducting the study. Results: In the study, it was found that the vast majority of nurses did not receive training to improve effective speaking skills (76.6%). It was determined that the mean ESS score was 98.40±11.08, and that the average score of the nurses who received training on effective speech skills was higher (p<0.05). Conclusion: In the study, it was determined that the nurses had moderately effective speech skills, and the average ESS score of the nurses who received training on effective speech skills was found to be higher. According to the results of the study, nurses should be supported both in their formal education and working life with activities such as domestic or foreign courses, symposiums, seminars, congresses, etc. in order to improve their effective speech skills professionally.